Electro‐Drawn Drug‐Loaded Biodegradable Polymer Microneedles as a Viable Route to Hypodermic Injection. (24th February 2014) - Vecchione, Raffaele; Coppola, Sara; Esposito, Eliana; Casale, Costantino; Vespini, Veronica; Grilli, Simonetta; Ferraro, Pietro; Netti, Paolo Antonio
<x xml:space="preserve">Abstract</x> Hypodermic needle injection is still the most common method of drug delivery despite its numerous limitations and drawbacks, such as pain, one‐shot administration, and risk of infection. Seeking a viable, safe, and pain‐free alternative to the over 16 billion injections per year has therefore become a top priority for our modern technological society. Here, a system that uses a pyroelectric cartridge in lieu of the syringe piston as a potential solution is discussed. Upon stimulation, the cartridge electro‐draws, at room temperature, an array of drug‐encapsulated, biodegradable polymer microneedles, able to deliver into hypodermic tissue both hydrophobic and hydrophilic bioactive agents, according to a predefined chrono‐programme. This mould‐free and contact‐free method permits the fabrication of biodegradable polymer microneedles into a ready‐to‐use configuration. In fact, they are formed on a flexible substrate/holder by drawing them directly from drop reservoirs, using a controlled electro‐hydrodynamic force. Tests of insertion are performed and discussed in order to demonstrate the possibility to prepare microneedles with suitable geometric and mechanical properties using this method.